Modeling and optimization of extraction process of eucalyptus essential oil (Eucalyptus globulus) - Moreno, Jeancarlos (2010)
In this paper we have studied the effect of the moisture from the eucalyptus leaf and the time of extraction on the yield of essential oil and the production cost. We took into account parameters such as steam temperature, pressure extraction, porous bed, steam flow and temperature of condensation. A Central Composite Rotational Design was used to evaluate optimum extraction areas and the cost that would follow, searching always to increase yields and reduce costs. According to this design, the extraction with the lowest production costs (0.57 Nuevos Soles by mL of essential oil) is reached when the leaves have moisture between 25 and 30% and are extracted with times between 98 and 126 min.